Investigating the multi-target therapeutic mechanism of Guihuang formula on Chronic Prostatitis. (10th August 2022) - Liu, Shengjing; Zhao, Feng; Deng, Yingjun; Zeng, Yin; Yan, Bin; Guo, Jun; Gao, Qinghe
Abstract: Ethnopharmacological relevance: Chronic prostatitis (CP) is a complex, intractable and prevalent urological disorder in men with no effective treatment. Guihuang formula (GHF) is a traditional Chinese medicine compound that is advantageous as a CP treatment, but its aetiology is poorly understood. Research and exploration of the mechanism of GHF will help the development of a potentially valuable drug for CP and provide deeper insight into CP. Aim of the study: To examine and further clarify the multi-target therapeutic mechanism of GHF on CP. Materials and methods: The chemical components in GHF were identified using UPLC-Q/TOF-MS. The active components and potential targets of GHF for the treatment of CP were screened and analyzed using network pharmacology and molecular docking. We constructed a CP rat model to investigate the therapeutic effect of GHF on CP and verify the influence of key targets and core pathways based on the results of network pharmacology. Results: A total of 143 ingredients were identified in GHF using UPLC-Q/TOF-MS, and 111 potential targets for GHF of CP were predicted. The "drug-ingredient-target-pathway" network was constructed and in compliance with the "Jun-Chen-Zuo-Shi" principle. GHF significantly reduced the prostate index, alleviated histological damage in the prostate, decreased CD3 + T cells and CD45 + leukocyte infiltration in the prostate, downregulated the expression of the proinflammatory cytokines IL-1β, IL-6, IL-18, COX-2, MCP-1 and TNF-α, decreased ROS levels and alleviated the production of MDA accompanied by an increase of SOD and GSH-PX levels. Meanwhile, GHF suppressed apoptosis in macrophages, downregulated the mRNA levels of PI3K, AKT and P6 5 NF -κB and inhibited the phosphorylation of the PI3K, AKT and P65 NF-κB. Conclusion: A network pharmacology and experimental validation-based strategy was used to elucidate the underlying "multicomponent, multitarget, and multipathway" mode of action of GHF against CP. We verified that GHF inhibited oxidative stress and inflammatory response, suppressed apoptosis in macrophages, inhibited the activation of the inflammation-related PI3K/AKT/NF-κB pathway in CP rat. These findings extend the conventional views of "one drug hits one target", and offer novel insights and indication paradigm for the future discovery on the multi-target therapeutic mechanism of traditional Chinese medicine compound. Graphical abstract: Image 1